(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This note intends to concentrate dispersed information, as for data of testimonial, bibliographic and referential orders that guide an analysis about the history of the Ambrosio Oropeza auditorium of the Universidad Centroccidental Lisandro Alvarado, with the intention of serving as orientation in a formal investigation and of greater amplitude on the subject that must be carried out based on the institutional documentary funds. Translated with DeepL.com (free version)